If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-8m + 2) = -434 Reorder the terms: 7(2 + -8m) = -434 (2 * 7 + -8m * 7) = -434 (14 + -56m) = -434 Solving 14 + -56m = -434 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -56m = -434 + -14 Combine like terms: 14 + -14 = 0 0 + -56m = -434 + -14 -56m = -434 + -14 Combine like terms: -434 + -14 = -448 -56m = -448 Divide each side by '-56'. m = 8 Simplifying m = 8
| 4=-(x-7)+3 | | 21dy+6xy-6xv-21dv= | | 8x+(-5)=35 | | Y=1.03x | | 2y+3y+30+4x-100+x+5=360 | | f(1)=1(1)+3 | | vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 | | 8p-6(1-2p)=86 | | x+(x+2)=116 | | n+4.1n+6=-1.5(n+4.8) | | -3(4x-8)=2-4(3x-7) | | -16x^2+64x-26=0 | | 3x-8=-24 | | 8p-6(1-2b)=86 |